2012
DOI: 10.1121/1.3688511
|View full text |Cite
|
Sign up to set email alerts
|

Sentence recognition in noise promoting or suppressing masking release by normal-hearing and cochlear-implant listeners

Abstract: Normal-hearing (NH) listeners maintain robust speech understanding in modulated noise by "glimpsing" portions of speech from a partially masked waveform-a phenomenon known as masking release (MR). Cochlear implant (CI) users, however, generally lack such resiliency. In previous studies, temporal masking of speech by noise occurred randomly, obscuring to what degree MR is attributable to the temporal overlap of speech and masker. In the present study, masker conditions were constructed to either promote (þMR) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 34 publications
(39 reference statements)
1
36
2
Order By: Relevance
“…One of the common findings from the studies of CI users is individual variability in their speech recognition scores regardless of speech materials or noise conditions (e.g., Fu & Galvin, 2008;Gifford, Shallop, & Peterson, 2008;Kwon et al, 2012), which was also found in the current study. Table 6 shows the performance of individual CI listeners in several conditions: quiet with full-spectrum speech and low-pass filtered speech, remote noise for the three AM conditions, and embedded noise for the same AM conditions.…”
Section: Clinical Implications For CI Listenerssupporting
confidence: 67%
See 2 more Smart Citations
“…One of the common findings from the studies of CI users is individual variability in their speech recognition scores regardless of speech materials or noise conditions (e.g., Fu & Galvin, 2008;Gifford, Shallop, & Peterson, 2008;Kwon et al, 2012), which was also found in the current study. Table 6 shows the performance of individual CI listeners in several conditions: quiet with full-spectrum speech and low-pass filtered speech, remote noise for the three AM conditions, and embedded noise for the same AM conditions.…”
Section: Clinical Implications For CI Listenerssupporting
confidence: 67%
“…Previous studies have reported that NH listeners' speech recognition scores could improve by as much as 80 percentage points when noise was modulated versus steady (Jin & Nelson, 2006). However, significant masking release reduction or no masking release has been found in cochlear implant (CI) users or in NH listeners identifying vocoded speech that simulates speech processed by a CI device (NH-Sim; Fu & Nogaki, 2004;Kwon, Perry, Wilhelm, & Healy 2012;Nelson & Jin, 2004;Nelson, Jin, Carney, & Nelson, 2003;Qin & Oxenham, 2003;Stickney, Zeng, Litovsky, & Assmann, 2004). For example, Nelson and colleagues (Nelson & Jin, 2004;Nelson et al, 2003) compared the performance of three listener groups (NH, CI, and NH-Sim) for sentence recognition in the presence of different masking noises, including steady-state noise and gated noise modulated at different frequencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that temporally interpolated noise, even at very high levels, had little effect on sentence recognition using masking-release conditions similar to those of Kwon et al [(2012). J. Acoust.…”
mentioning
confidence: 97%
“…These studies indicate that intelligibility is increased when fluctuations are introduced to a masker (e.g., Miller, 1947b;Carhart et al, 1966), thus providing glimpses of speech in the masker dips. Kwon et al (2012) examined MR under conditions specifically designed to promote or suppress it. In one condition (-MR), masker fluctuations occurred simultaneously with speech-energy fluctuations, thus maximizing the masking of speech by noise and minimizing MR.…”
Section: Introductionmentioning
confidence: 99%